Abses dentogen subkutan - Fonny Dahong (Journal of Dentomaxillofacial Science, 2009)
Subcutaneous mandibular abscess is an acute lesion characterized by localization ofpus in the structures surround the mandibular jaw and spreads into soft tissue underskin. Most patients are treated with antibiotics, analgetics, and drainage. Surgicaldrainage of abscess is usually indicated when the abscess has developed from a hardserous inflammation to a soft pus stage. Untreated abscess may worsen and lead tolife-threatening complications.